Of boundaries, orders, and security. Starting from Der Bau - Danani, Carla (Itinerari, 2024)
The text is developed in three passages. Firstly, it highlights, in Kafka’s text Der Bau, a provocative invitation to decentralise, to put oneself in a place other than the one in which one is settled. Taking it up means the effort of practising a “jutting out”, the risk of exercising a divestment of the obvious, the habitual, the taken for granted. In such a way, one then accesses what is familiar by understanding that it is not for this reason also known – as Hegel said (weil es bekannt ist, nicht erkannt). It must, therefore, still be questioned. This is precisely the case with building. A second passage then considers the perspective of building as a search for security, while a third finally delves into the horizons of meaning, exploring the complex dynamic between order and extraneousness. The result is the subversion of customary and reassuring binarisms but, at the same time, also the suggestion, admittedly risky, of alternative generous possibilities.